Implementation of The Women Farmers' Group (KWT) Program In Marpoyan Damai District, Pekanbaru City - salsha; MUHAMMAD IHSAN (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2026)
The Women Farmers’ Group (KWT) is a community-based institutional mechanism that plays a strategic role in women’s empowerment in the agricultural sector. This study aims to examine the implementation of the KWT program in Marpoyan Damai Subdistrict, Pekanbaru City, and to identify its benefits for members and related stakeholders. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, focus group discussions, and documentation involving 7 informants selected through purposive sampling. Data analysis followed the Miles et al. (2014) model comprising three stages: data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation. The results indicate that the KWT program contributes to increased agricultural knowledge, crop processing skills, and household income among members. However, the program’s sustainability remains constrained by limited capital, low digital literacy, and restricted market access. The main contribution of this study is the formulation of a hybrid social group typology for urban KWT, which integrates productive economic functions, women’s empowerment, and ecological restoration within a single interconnected system extending the conventional understanding of KWT beyond subsistence farming toward a multifunctional agent of change relevant to urban agricultural contexts in Indonesia